Underwater pipeline impact localization using piezoceramic transducers. (12th September 2017) - Zhu, Junxiao; Ho, Siu Chun Michael; Patil, Devendra; Wang, Ning; Hirsch, Rachel; Song, Gangbing
Abstract: Reports indicated that impact events accounted for 47% of offshore pipeline failures, which calls for impact detection and localization for subsea pipelines. In this paper, an innovative method for rapid localization of impacts on underwater pipelines utilizing a novel determination technique for both arrival-time and group velocity (ATGV) of ultrasonic guided waves with lead zirconate titanate (PZT) transducers is described. PZT transducers mounted on the outer surface of a model pipeline were utilized to measure ultrasonic guided waves generated by impact events. Based on the signals from PZT sensors, the ATGV technique integrates wavelet decomposition, Hilbert transform and statistical analysis to pinpoint the arrival-time of the designated ultrasonic guided waves with a specific group velocity. Experimental results have verified the effectiveness and the localization accuracy for eight impact points along a model underwater pipeline. All estimations errors were small and were comparable with the wavelength of the designated ultrasonic guided waves. Furthermore, the method is robust against the low frequency structural vibration introduced by other external forces.